Spiny lobster development: mechanisms inducing metamorphosis to the puerulus: a review - McWilliam, P.; Phillips, Bruce (Springer, 2007)
This review outlines current knowledge of mechanisms effecting metamorphosis in decapod crustaceans and insects. The comparative approach demonstrates some of the complexities that need resolving to find an answer to the question raised frequently by ecologists: “What triggers metamorphosis in spiny lobsters?” It is evident that crustacean moulting and metamorphosis are genetically controlled through endocrine systems that mediate gene expression. The molecular mechanisms underlying these developmental processes have been studied intensively in insects, particularly in the fruitfly, Drosophila melanogaster (Diptera), and some lepidopteran species. Comparatively, there is minimal information available for a few decapod crustacean species, but none for spiny lobsters (Palinuridae). Nothing was known of hormone signalling transduction pathways, via nuclear receptors (NRs) and gene activation during larval moults in palinurids—until a recent, ground-breaking study of early phyllosomal development of Panulirus ornatus by Wilson et al. (Rock Lobster Enhancement and Aquaculture Subprogram. FRDC Project 2000/263, Australian Govt, Fisheries Research and Development Corporation and Australian Institute of Marine Science, Nov 2005). Their study not only identified homologues of five hormone NRs of D. melanogaster, but also patterns of gene regulation showing strong similarities to those of gene expression found in insect larval development. Their results indicated that control of moulting and metamorphosis in palinurids closely parallels that in insects, suggesting that insects can serve as model systems for elucidating molecular mechanisms in larval decapods. In insects and crustaceans, the steroid hormone, ecdysone, (20E) initiates moulting. In insects, juvenile hormone (JH) mediates the type of larval moult that occurs, either anamorphic or metamorphic. The latter results when the level of JH in the haemolymph drops in the final larval instar. High levels of JH inhibit the metamorphic moult during insect larval development. The interaction of 20E and JH is not fully understood, and the operative molecular mechanisms are still being elucidated. No nuclear receptor for JH has been identified, and alternative JH signalling pathways await identification. In decapod crustaceans, methyl farnesoate (MF), a precursor of JH, replaces the latter in other functions mediated by JH in insects; but there is little evidence indicating that MF plays a similar ‘antimetamorphic’ role in decapod larval moults.